The effects of 12 weeks of chiropractic spinal adjustments on physiological biomarkers in adults: A pragmatic randomized controlled trial - Imran Amjad; Imran Khan Niazi; Nitika Kumari; Usman Ghani; Usman Rashid; Felipe Coutinho Kullmann Duarte; Federico Fortuna; Silvia Iglesias; Diego Gonzalez; Alex Sumich; Bibiana Fabre; Kelly Holt; et al. (PLoS ONE, 2025)
Background Longer-term effects of chiropractic care on neuroplasticity, stress, and immune biomarkers remain unclear. Objective This study evaluates the effects of chiropractic care on physiological biomarkers, including brain-derived neurotrophic factor (BDNF), cortisol (saliva, blood, hair), and inflammatory cytokines [interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), interferon-gamma (IFN-γ), C-reactive protein (CRP), B-lymphocytes (CD19), T-helper cells (CD4), cytotoxic T cells (CD8), and natural killer cells (CD56)] in subclinical spinal pain patients. Methods Parallel-group, pragmatic randomized controlled trial conducted at the Rehabilitation Center of Railway General Hospital, Rawalpindi, Pakistan. Intervention: 12 weeks; follow-up: 16 weeks (May–December 2022). Participants with subclinical spinal pain were randomly assigned by using simple lottery method to either 12 weeks of chiropractic or sham care. We aimed to recruit up to 150 participants over three months; however, given the pragmatic nature of the trial and logistical constraints, including the availability of chiropractors, the final number enrolled was determined by how many eligible participants could be recruited during this time. Adults aged 20–60 years with subclinical spinal pain (n = 106 randomized; 88 completed 12-week measures; 73 completed 16-week follow-up). Among those who finished 12 weeks: chiropractic, 26 males/15 females, mean age 37.49 ± 12.39 years; sham, 24 males/23 females, mean age 26.85 ± 7.13 years. The primary outcome blood BDNF and secondary outcome, including saliva, blood and hair cortisol, IL-6, TNF-α, IFN-γ, CRP, CD19, CD4, CD8, and CD56 levels were measured at baseline, after 12 weeks of intervention, and at a 16-week follow-up. Linear and linear mixed-effects regression models were used to assess the effect of care and time on biological measures. Results Significant between-group differences were observed after 12 weeks of intervention, with higher salivary cortisol 5 ± 2 [0, 10], p = 0.045 and blood BDNF150 ± 60 (40, 270), p = 0.009 and IL-6 1.0 ± 0.3 [0.5, 1.5], p < 0.001 levels in the chiropractic care group. At the 16-week follow-up, blood cortisol −9 ± 4 [−17, −1], p = 0.024, IFN-γ − 22 ± 7 [−35, −9], and TNF-α −2 ± 1 [−5, 0], p = 0.028 levels increased in the sham group. Within-group comparisons showed a non-significant 10 ± 20 [−20, 50], p = 0.439 reduction in hair cortisol levels in the chiropractic group at 12 weeks, along with increased levels of blood cortisol, BDNF, CD8, CD4, IL-6, and CD19. Conclusion 12 weeks of Chiropractic care modulates biomarkers linked to neuroplasticity, inflammation, and stress. Increases in brain-derived neurotrophic factor and interleukin-6 suggest enhanced neuroplasticity and inflammatory responses, while decreases in tumor necrosis factor-alpha indicate a regulatory effect on systemic inflammation. These findings support the notion that chiropractic care modulates physiological systemic biomarkers, which may underscore its benefits on clinical outcomes. Trial registration ClinicalTrials.gov NCT05369156 .